Towards the hard problem of skill acquisition - Moe, V. F. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction A crucial task for sport research is to understand and explain the processes and conditions underlying skillful motor behavior. One way to carve out the processes and conditions behind skillful motor behavior is to describe and analyze differences (and similarities) between the distinct stages of skill acquisition. The paper starts by describing, comparing and analyzing two models of skill acquisition as a step towards the final target of the paper - to identify the hard problem of skill acquisition. Methods This is a work in the philosophy of sport. Consequently, it is grounded in the distinctive character of traditional philosophy. The paper uses both phenomenological descriptions and conceptual analysis to accomplish a critical systematization and examination of examples, concepts and arguments relevant to the understanding of skillful motor behavior in sport. Results Fitts` 1 three phase model and Dreyfus` five stage [2] model of skill acquisition is elaborated. Both models account for intellectual and bodily skills. Fitts` model is one of the most influential conceptualization of the skill learning process in sport research [e.g., 3, 4]. It incorporates an early cognitive phase, an intermediate associative phase and a late autonomous phase [5]. Dreyfus` model is constituted by the following five stages: novice, advanced beginner, competence, proficiency and expertise. Sport research is less familiar with Dreyfus` account, but with its five stages, it offers a more detailed phenomenology of the skill learning process compared to Fitts` three phase model. Discussion/conclusion The discussion emphasizes differences and similarities between the two models of skill acquisition presented above. Emerging from this discussion, the paper identifies one vital problem that is referred to as the hard problem of skill acquisition. The main intuition at work is that a clearly stated and well-defined problem area may be the most efficient mean to produce a comprehensive and coherent theory of skillful motor behavior in the future.